PPAR-γ агоністи - модулятори інсуліночутливості - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2008)
Three month treatment with Pioglar showed statistically relevant improvement of the certain markers, which depicted insulin resistance, inflammation process and dislipidemia. Decrease in glucose, insulin, HbA1c and HOMA-index were documented. Elevation of high density lipoproteins was discovered following Pioglar use. Improvement of peripheral insulin sensitivity was proved